Requirement of energy and protein of beef cattle on tropical pasture - doi: 10.4025/actascianimsci.v35i4.21143 - Eriton Egidio Lisboa Valente; Mário Fonseca Paulino; Edenio Detmann; Sebastião de Campos Valadares Filho; Javier Enrique Garces Cardenas; Isabela Fernanda Teixeira Dias (Acta Scientiarum. Animal Sciences, 2013)
Protein and energy requirements of beef cattle, aged between 4 and 18 months old, on tropicalpastures, were estimated. Forty-six Nellore calves (138.3 ± 3.4 kg BW and 90-150 days old), kept on pasture,were distributed in a maintenance group (restricted feeding) or in nutritional plans, receiving a supplements withdifferent amounts of protein and carbohydrate or non-supplemented. The net energy requirement for weightgain (NEg) was obtained by linear regression of logarithm of retained energy as a function of logarithm of emptybody weight gain. The net energy requirement for maintenance (NEm) was estimated by the exponential relationbetween heat production and metabolizable energy intake. Net protein requirement for weight gain (RP) wasestimated by multiple linear regression of retained protein in the weight gain of empty body (EBWG) andretained energy. The efficiency of metabolizable energy (ME) used for maintenance and for weight gain was 0.55and 0.26, respectively. The ME requirement for maintenance was 124 kcal EBW-0.75. RP decreased in proportionto body weight increase. NEg and RP may be obtained by equations: RE (Mcal kg-1) = 0.044 x EBW0.75 xEBWG1.1302 and RP (g day-1) = -31.45 + 229.69 x EBWG – 8.75 x RE, respectively.